2021
DOI: 10.1111/eci.13561
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium supplementation reduces inflammation in rats with induced chronic kidney disease

Abstract: Background: Inflammation is a common feature in chronic kidney disease (CKD) that appears specifically associated with cardiovascular derangements in CKD patients.Observational studies have revealed a link between low Mg levels and inflammation. In this study, we hypothesize that Mg might have a modulatory effect on the inflammation induced under the uremic milieu.Methods: In vivo studies were performed in a 5/6 nephrectomized rat model of CKD. Furthermore, a possible direct effect of Mg was addressed through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…It has been widely used to study the therapeutic effect of drugs on CKD. 37–39 Moreover, the 5/6 nephrectomy model also show significant gut microbiota dysbiosis, 40 , 41 and this model may be suitable in this study.…”
Section: Discussionmentioning
confidence: 92%
“…It has been widely used to study the therapeutic effect of drugs on CKD. 37–39 Moreover, the 5/6 nephrectomy model also show significant gut microbiota dysbiosis, 40 , 41 and this model may be suitable in this study.…”
Section: Discussionmentioning
confidence: 92%
“…At present, the 5/6 nephrectomy model has been recognized as the classical model most similar to human CKD. It has been widely used to study the therapeutic effect of drugs on CKD ( Mizukami et al, 2019 ; López-Baltanás et al, 2021 ; Zhou et al, 2021 ). Moreover, the 5/6 nephrectomy model also show significant gut microbiota dysbiosis ( Liu et al, 2018 ; Feng et al, 2019 ), and this model may be suitable in this study.…”
Section: Discussionmentioning
confidence: 99%
“… Xie et al (2019) reported that magnesium isoglycyrrhizinate suppresses LPS-induced inflammation and oxidative stress by inhibiting NF-κB and MAPK pathways in RAW264.7 cells ( Xie et al, 2019 ). Lopez-Baltanas et al (2021) found that magnesium supplementation reduces inflammation in rats with induced chronic kidney disease ( Lopez-Baltanas et al, 2021 ). Moreover, magnesium sulfate differentially modulates fetal membrane inflammation in a time-dependent manner ( Cross et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%